2020
DOI: 10.55724/j.biofar.trop.v3i2.278
|View full text |Cite
|
Sign up to set email alerts
|

Uji Efektivitas Sediaan Gel Ekstrak Batang Pepaya (Carica papaya L.) Sebagai Penyembuh Luka Sayat Pada Tikus Putih (Rattus novergicus).

Abstract: Tanaman obat berkembang pesat dikalangan masyarakat karena tanaman obat berkhasiat untuk menyembuhkan berbagai penyakit. Salah satu tanaman obat yang berkembang adalah tanaman batang pohon pepaya (Carica papaya L.) yang terbukti mampu mempercepat penyembuhan luka. Penelitian ini bertujuan untuk mengetahui efektivitas pemberian gel ekstrak batang pepaya terhadap proses penyembuhan luka sayat pada tikus putih (Rattus novergicus). Hewan uji yang digunakan adalah tikus berjumlah 15 ekor, berjenis kelamin jantan. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The analysis results are supported by previous studies that showed papaya leaves could be used as an antiseptic in the form of a gel. The preparation gel with papaya leaf extract levels starting from 10% can reduce microorganisms by up to 57% (Watung et al, 2020).…”
Section: Medical Laboratory Technology Journal |mentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis results are supported by previous studies that showed papaya leaves could be used as an antiseptic in the form of a gel. The preparation gel with papaya leaf extract levels starting from 10% can reduce microorganisms by up to 57% (Watung et al, 2020).…”
Section: Medical Laboratory Technology Journal |mentioning
confidence: 99%
“…Myofibroblast cells commonly found in wound contraction consist of actin and myosin equal to the contraction system in smooth muscle so that myofibroblasts can contract and elongate. Wound contraction that occurs in the late stages of wound healing looks like the changes in the shape of the wound and the reduction of the open wound area and produces a smaller wound area (Watung et al, 2020).…”
Section: Medical Laboratory Technology Journal |mentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, superworm can live well when given organic feed intake (van Broekhoven et al, 2015), especially feed with fibre above 5% (Li et al, 2016). Papaya stems as superworm feed are believed to provide not only fibre but also produce quality superworms, given the presence of antibacterial content in papaya stems (Handayani et al, 2020;Nirmala et al, 2022;Watung et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the use of herbal therapy is increasingly popular because apart from being effective, it also tends to have a very low risk of side effects. One of the plants that is receiving great attention is the papaya plant, because various parts such as leaves, fruit, stalks, stems and roots have a number of benefits in a medicinal context (Syahruddin, 2019).…”
Section: Introductionmentioning
confidence: 99%